Comparison of double intravenous vasopressor automated system using nexfin versus manual vasopressor bolus administration for maintenance of haemodynamic stability during spinal anaesthesia for caesarean delivery: A randomised double-blind controlled trial. Issue 5 (May 2018) - Sng, Ban Leong; Du, Wei; Lee, Man Xin; Ithnin, Farida; Mathur, Deepak; Leong, Wan Ling; Sultana, Rehena; Han, Nian-Lin R.; Sia, Alex Tiong Heng
Abstract : BACKGROUND: Hypotension is a common side effect of spinal anaesthesia during caesarean delivery and is associated with maternal and foetal adverse effects. We developed an updated double intravenous vasopressor automated (DIVA) system that administers phenylephrine or ephedrine based on continuous noninvasive haemodynamic monitoring using the Nexfin device. OBJECTIVE: The aim of our present study is to compare the performance and reliability of the DIVA system against Manual Vasopressor Bolus administration. DESIGN: A randomised, double-blind controlled trial. SETTING: Single-centre, KK Women's and Children's Hospital, Singapore. PATIENTS: Two hundred and thirty-six healthy women undergoing elective caesarean delivery under spinal anaesthesia. MAIN OUTCOME MEASURES: The primary outcome was the incidence of maternal hypotension. The secondary outcome measures were reactive hypertension, total vasopressor requirement and maternal and neonatal outcomes. RESULTS: The DIVA group had a significantly lower incidence of maternal hypotension, with 39.3% (46 of 117) patients having any SBP reading less than 80% of baseline compared with 57.5% (65 of 113) in the manual vasopressor bolus group ( P = 0.008). The DIVA group also had fewer hypotensive episodes than the manual vasopressor bolus group (4.67 versus 7.77%; P < 0.0001). There was no difference in the incidence of reactive hypertension or the total vasopressor requirement. The DIVA group had less wobble in system performance. Maternal and neonatal outcomes were similar. CONCLUSION: The DIVA system achieved better control of maternal blood pressure after spinal anaesthesia than manual vasopressor bolus administration. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT02277730.